The Case for an Authentic Growth - Yen Ong (Oz, 2018)
I have sold out since I graduated a little more than two decades ago. My idealistic, younger self would have patently condemned the choices my present self has made since then. Idealism would be the righteous position for a student of architecture to take, one who has been fed stories of famed architects realizing their architectural vision in no other way but theirs, proclaiming an absolute authenticity to their creation, or opt - ing to be financially bankrupt rather than to compromise their talents in service of uninspiring commissions. That was then, and this is now: the authentic identity that drives one’s body of work matures over time and is their inescapable reality.